Hereditary Breast and Ovarian Cancer: Factors Influencing the Uptake of Preventative Surgeries among BRCA1 and BRCA2 Mutation Carriers - Bobrowski, David; Hu, David (The Meducator, 2018)
Genetic testing for breast cancer 1 (BRCA1) and breast cancer 2 (BRCA2) mutations in clinical oncology is becoming more widely employed around the world. Testing allows clinicians to determine if unaffected highrisk women carry a BRCA mutation, and if preventive care in the form of prophylactic procedures and/or increased surveillance is advisable. As well, identifying carrier status can aid physicians in tailoring the best treatment for affected women with breast or ovarian cancer. However, studies have shown that the uptake of preventive strategies, particularly risk-reducing surgeries, among unaffected women found to carry a BRCA mutation is influenced by a number of factors. These include cost of genetic testing, cancer-related distress, patient consultation, perceived benefits and risks of invasive surgery, and level of education. To alleviate these emotional and cognitive barriers, clinicians should ensure women carrying a BRCA mutation are well-informed about available treatments and potentially fatal outcomes associated with breast and ovarian cancer.